Goodness.
forcegravity= GMassmoon*massyou/r^2
forcegravity/massyou = GMassmoon/r^2
"g"= G*Massmoon/r^2
acceleartiononmoon= GMassmoon/radius^2
=G 7.35E22/(1.74E6)^2= G 2.43E10=
= 6.67E-11*2.43E10=
1.62 m/s^2 or as a gravitational field constant= 1.62 N/kg
I have no idea why you used the mass of Earth.
were did you get
a = r^-2 Gm
from
i thought that the equation was
net force = m a = Fg = r^-2 G m m2
5 answers
ok net force = m a
only force present
force of gravity
Fg = mg = r^-2 G m M
were m is the mass of the moon and the M is the mass of what ever it's orbiting...
correct?
Fg = mg = r^-2 G m M
divide both sides by the mass of the moon
g = r^-2 G M
so I guess I just don't get it
why would we say that the force of gravity often called weight of the moon is the mass M (what ever mass the moon is orbiting) times acceleration
force of gravity acting on the moon is equal to the Mg that's the only way we can cancel out the second mass but why would we say that the force of gravity acting on the moon is equal to the mass of the moon times gravity...
only force present
force of gravity
Fg = mg = r^-2 G m M
were m is the mass of the moon and the M is the mass of what ever it's orbiting...
correct?
Fg = mg = r^-2 G m M
divide both sides by the mass of the moon
g = r^-2 G M
so I guess I just don't get it
why would we say that the force of gravity often called weight of the moon is the mass M (what ever mass the moon is orbiting) times acceleration
force of gravity acting on the moon is equal to the Mg that's the only way we can cancel out the second mass but why would we say that the force of gravity acting on the moon is equal to the mass of the moon times gravity...
you don't get it.
Divide the force of gravity by the mass of the object which is being accelerated.
F/massyou = your acceleration
of course, forces come in couplets, so
F/massmoon= moons acceleration toward you.
where F is the force of gravity, it operates on you and the moon, opposite directions.
Divide the force of gravity by the mass of the object which is being accelerated.
F/massyou = your acceleration
of course, forces come in couplets, so
F/massmoon= moons acceleration toward you.
where F is the force of gravity, it operates on you and the moon, opposite directions.
Fg exerted by whatever it's orbiting onto moon = r^-2 G (mass of moon) M = to the gravitional force exerted by moon onto M = Mg
ok then you can divide by M
but
why is it the force of gravity exerted by the moon onto whatever it's orbiting mass M just equal to Mg ???
Please I think I almost got it
ok then you can divide by M
but
why is it the force of gravity exerted by the moon onto whatever it's orbiting mass M just equal to Mg ???
Please I think I almost got it
ok i get it see new question